Identifying data gaps in early childhood physical activity evidence - Wimberly, Jessica; Nguyen, Aleah; Memoli, Erica; Kasman, Matt; Heerman, Bill; Pate, Russell; Sommer, Evan; Sedlak, Adam; Reader, Lydia; Hammond, Ross A.; Barkin, Shari (Frontiers in Pediatrics, 2024)
Childhood physical activity sets the foundation for health. While we know many factors that contribute to physical activity, there are limitations in our knowledge, especially in early childhood. Through our review, we identify gaps in existing datasets to guide future research.